2013
DOI: 10.18778/7525-895-0
|View full text |Cite
|
Sign up to set email alerts
|

Optical cues used in prey identification by a juvenile jumping spider, Yllenus arenarius (Araneae, Salticidae)

Abstract: REVIEWER Frank ZachosTYPESETTING Maciej Bartos COVER DESIGN Joanna Skopińska COVER PHOTO Adult female of Yllenus arenarius with a captured fly (photo by Maciej Bartos)Printed directly from camera-ready materials provided to the Łódź University Press

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 81 publications
(199 reference statements)
0
2
0
Order By: Relevance
“…Although a few individuals chose the circle (roughly half the number that chose the other stimuli), it is not entirely surprising that the spiders categorise the circle as a prey item. Many generalist predators, including some salticids, categorise stimuli as prey using only basic key features (Drees 1952;Barlow 1953;Lettvin et al 1959;Heinze et al 1998;Prete et al 2011;Bartos 2013). What is somewhat surprising was the high attrition rate in this experiment, as salticids typically readily respond to stimuli in the lab (Harland et al 1999).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Although a few individuals chose the circle (roughly half the number that chose the other stimuli), it is not entirely surprising that the spiders categorise the circle as a prey item. Many generalist predators, including some salticids, categorise stimuli as prey using only basic key features (Drees 1952;Barlow 1953;Lettvin et al 1959;Heinze et al 1998;Prete et al 2011;Bartos 2013). What is somewhat surprising was the high attrition rate in this experiment, as salticids typically readily respond to stimuli in the lab (Harland et al 1999).…”
Section: Discussionmentioning
confidence: 85%
“…Bednarski et al 2012show that the salticid Phidippus audax (Hentz, 1845) uses stimulus movement as the key element for categorisation as prey, thus adopting a very large perceptual envelope of this category (including a moving rectangle). In a similar set of studies, Bartos (2007Bartos ( , 2013 showed that the salticid Yllenus arenarius Menge 1868 uses four key elements (stimulus length, movement type, congruent location of body parts and number of appendages) for the classification of a stimulus as prey. Furthermore, stimulus length and type of movement are used for classification into two prey categories with distinct escape risks requiring different attack strategies.…”
Section: Discussionmentioning
confidence: 99%